Penerapan Hipnosis Lima Jari untuk Menurunkan Ansietas pada Pasien Pre Operasi - Bimo Cahya Pambudi; Sri Indaryati; Keristina Ajul (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Preoperative anxiety is a common issue that can affect both the physical and psychological condition of patients before undergoing surgery. One non-pharmacological intervention that can be applied to reduce anxiety is the five-finger hypnosis therapy.Evaluating the effectiveness of five-finger hypnosis therapy in reducing anxiety levels in preoperative patients at Siloam Silampari Hospital, Lubuklinggau.Using a case study approach with the application of evidence-based nursing practice in nursing care for three preoperative patients experiencing anxiety. Data were collected through nursing assessments and measured using the Hamilton Anxiety Rating Scale (HARS) to determine anxiety levels. The intervention was carried out over three days following standard operating procedures (SOP).The study results indicate that five-finger hypnosis therapy is effective in reducing anxiety levels in preoperative patients. The HARS scores gradually decreased, with all patients improving from severe anxiety to mild anxiety and eventually showing no clinically significant anxiety by the third day of the intervention. A more significant impact was observed after the second and third days of intervention, suggesting that this therapy is more effective when applied repeatedly and consistently.